2021
DOI: 10.15585/mmwr.mm7016e1
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Modeling of SARS-CoV-2 Exposure Reduction Through Physically Distanced Seating in Aircraft Cabins Using Bacteriophage Aerosol — November 2020

Abstract: On April 14, 2021, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).Aircraft can hold large numbers of persons in close proximity for long periods, which can increase the risk for transmission of infectious disease.* Current CDC guidelines recommend against travel for persons who have not been vaccinated against COVID-19, and a January 2021 CDC order requires masking for all persons while on airplanes. †, § Research suggests that seating proximity on aircraft is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 9 publications
(7 reference statements)
0
18
0
2
Order By: Relevance
“…Airlines have discontinued such practices as air travel increased in recent months [ 25 ]. A recent study suggested that keeping middle seats empty lowers exposure (dose) significantly [ 26 ]. But it did not calculate the infection risk, account for passenger movement, or study the impact of masks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Airlines have discontinued such practices as air travel increased in recent months [ 25 ]. A recent study suggested that keeping middle seats empty lowers exposure (dose) significantly [ 26 ]. But it did not calculate the infection risk, account for passenger movement, or study the impact of masks.…”
Section: Resultsmentioning
confidence: 99%
“…Following PRCC methodology described in Refs. [ 26 , 27 ], we rank the uncertain parameters, κ and d 0 , in the sampling matrix together with the outcome measures. The PRCC measures the effect of each input parameter on outcome variable, assuming the parameters to be independent.…”
Section: A Distance To the Infective Personmentioning
confidence: 99%
“…Given that many of the routine laboratory procedures used to study and process virus samples (sample de-capping, pipetting, centrifugation, and mixing) exhibit high potential for producing aerosols 13 , 17 , 18 , it is important to adopt strict safety precautions when artificially aerosolizing virus particles using atomizers. Hence, it is preferable to generate aerosolized viruses at low concentrations to reduce health risks 16 , 19 and mimic the actual environment in which airborne virus particles are present as low concentrations 20 , 21 . Several studies indicate that SMPS results are affected by particle shape and morphology and by the upper and lower size limits set by the instrument 5 , 6 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In order to access small particles in the aerosol contamination, a bacteriophage for Escherichia coli previously isolated from domestic sewage samples was used [ 16 ]. The choice of a bacteriophage as a contamination model is due to its similar size to SARS-CoV-2 [ 17 ] and because this microorganism is harmless to humans.…”
Section: Methodsmentioning
confidence: 99%